How Well Can Educational Empowerment Affect Saudi Women’s Quality of Life? The Roles of Decision Making Power and the Economic Implications - Saleh Ahmed Saif Abdulmughni; Mohammed Hasan Ali Al-Abyadh (Journal of Educational and Human Sciences, 2023)
Women continue to experience inequality and vulnerability in the majority of sectors; they must always be supported in all aspects of their lives. In today's society, development rhetoric is shaped and directed by the purpose of empowering individuals and communities. The purpose of this study is to raise awareness among Saudi women about various forms of empowerment and to examine the role of educational empowerment to make powerful decisions to achieve economic gains for a better quality of life. The study's sample included 220 female students From the College of Arts and Sciences, and the College of Applied Medical Sciences, Prince Sattam Bin Abdulaziz University, Wadi Al-Dawasir Branch, in the KSA. The SmartPLS-SEM 4 was run to analyze the research data and validate the research hypotheses. The research findings assert that women’s educational empowerment drives better decision-making power that enables achieving substantial economic gains in terms of household gains and community gains and ultimately supports improved life quality. In addition to the positive significant relationships between the research variables, women’s economic household gains and women’s economic community gains were found to positively mediate the relationship between women’s decision-making empowerment and women’s improved life quality. The results of this study offer a theoretical contribution to the literature on gender and growth, showing that households headed by women achieve an enhanced economic rate enabled by their educational empowerment, decision-making power, and the gained economic implications. Practically speaking, this study informs policymakers of the steps that need to be taken to advance women's status in society in general.